2014
DOI: 10.2147/cwcmr.s59946
|View full text |Cite
|
Sign up to set email alerts
|

A new generation of topical chronic wound treatments containing specific MMP inhibitors

Abstract: Incidence of chronic wounds is constantly rising worldwide, but all currently available treatments are intended either to provide symptomatic relief or to assist cicatrization to some extent, but not to directly stimulate cellular growth. Physiologically, chronic wound healing simply requires cell growth to fill the injured cavity. To grow, our cells need to attach onto a cushion, called extracellular matrix (ECM), secreted by the mother cells and composed of multiple proteins. Recent scientific works prove th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…MMPs in the chronic wound are products of both the host and bacteria. Shrivastava et al have shown that the MMPs in pressure ulcers, diabetic ulcers and venous leg ulcers are more or less identical, which might explain why the chronic wounds with diverse etiologies that were treated with Aktisor® suspension healed [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMPs in the chronic wound are products of both the host and bacteria. Shrivastava et al have shown that the MMPs in pressure ulcers, diabetic ulcers and venous leg ulcers are more or less identical, which might explain why the chronic wounds with diverse etiologies that were treated with Aktisor® suspension healed [8].…”
Section: Discussionmentioning
confidence: 99%
“…Glycerol is also known as an anti-microbial substance, often used in medicine for preserving tissues and cells, and is therefore an excellent choice as a cleansing and moisturizing ingredient, being totally safe for topical application on wounds and having also demonstrated wound healing properties [1997 patent N˚PCT/FR99/01340; 2013 patent N˚PCT/EP2013/061835] [7]. The tannin-rich plant extract component stops and prevents the destructive action of MMPs in the wound bed, thus preserving the cell matrix integrity crucial to cellular attachment and cellular growth [8] [9]. Additionally, medical honey products have proved to be effective because they cleanse the wound and accelerate wound healing, even in immune-compromised patients with colonization of multi-resistant bacteria [10] [11].…”
Section: Introductionmentioning
confidence: 99%
“…Almost all systemic drugs induce side effects and cause more harm than good, whereas topically applying any chemical on the LRT would block the healing of damaged URT mucosa [28]. Taking into consideration the future research on mono-target anticough drugs, multiple side effects [29,30], development of bacterial resistance and inefficacy of antibiotics for the treatment of dry cough [31,32], F-VB-Gy opens a totally new horizon not only for the treatment of dry or wet cough, but potentially also for the treatment of other topical diseases having a multifactorial origin [33][34][35]. Further research is required to use this non-invasive technology for the treatment of other topical diseases for which there is still no effective treatment available.…”
Section: Discussionmentioning
confidence: 99%
“…A few patients of this study complained about moderate nasal irritation right after each TP application, lasting for about [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] seconds. This may be attributable to the fact that FPG solution is osmotic and draws intracellular hypotonic liquid as soon as it is sprayed as a film over the nasal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent instant dilution of the film a small quantity of VB-Gy binding plant extracts rich in polymeric tannins was added to it as experiments and studies conducted by our laboratory have shown that certain specific tannins bind to the VB-Gy molecules and create a flexible film with increased resistance to dilution resulting in improved duration of action [29]. Tannins are large, inert and highly branched molecules which do not interact with the cellular structures are noncytotoxic even at higher concentrations and they are easily expelled with hypotonic liquid flow once the FPG film is disintegrated.…”
Section: Discussionmentioning
confidence: 99%